An archaeal protein evolutionarily conserved in prokaryotes is a zinc-dependent metalloprotease. Issue 6 (15th October 2012) - Hu, Yongmei; Peng, Nan; Han, Wenyuan; Mei, Yuxia; Chen, Zhengjun; Feng, Xu; Liang, Yun Xiang; She, Qunxin
Abstract : A putative protease gene ( tldD ) was previously identified from studying tolerance of letD encoding the CcdB toxin of a toxin–antidote system of the F plasmid in Escherichia coli. While this gene is evolutionarily conserved in archaea and bacteria, the proteolytic activity of encoded proteins remained to be demonstrated experimentally. Here we studied Sso0660, an archaeal TldD homologue encoded in Sulfolobus solfataricus by overexpression of the recombinant protein and characterization of the purified enzyme. We found that the enzyme is active in degrading azocasein and FITC–BSA substrates. Protease inhibitor studies showed that EDTA and o -phenanthroline, two well-known metalloprotease inhibitors, either abolished completely or strongly inhibited the enzyme activity, and flame spectrometric analysis showed that a zinc ion is a cofactor of the protease. Furthermore, the protein forms disulfide bond via the Cys 416 residue, yielding protein dimer that is the active form of the enzyme. These results establish for the first time that tidD genes encode zinc-containing proteases, classifying them as a family in the metalloprotease class.